PENGARUH KOMITE AUDIT, INTENSITAS MODAL, UKURAN PERUSAHAAN DAN INTENSITAS ASET TETAP TERHADAP AGRESIVITAS PAJAK - Ramdani, Edon; Ardiansyah, M.F (LPPM Universitas Putera Batam, 2023)
This study aims to provide empirical evidence of the influence of the Audit Committee, Capital Intensity, Company Size, and Fixed Asset Intensity on Tax Aggressiveness. The population in this study consists of manufacturing companies in the Food and Beverage subsector for the years 2017-2022. The independent variables in this study are the Audit Committee as the First Independent Variable, Capital Intensity as the Second Independent Variable, Company Size as the Third Independent Variable, and Fixed Asset Intensity as the Fourth Independent Variable, with the dependent variable being Tax Aggressiveness. The research method used in this study is a quantitative method with sample determination using purposive sampling, resulting in a final sample of 9 companies observed over a period of 6 years, generating 54 observation data. The analysis technique, hypothesis testing, and hypothesis testing were conducted using panel data regression analysis with the assistance of E-views 12. The results of this study indicate that the selected model is the Common Effect Model. Based on data analysis, the research results show that the Audit Committee, Capital Intensity, Company Size, and Fixed Asset Intensity simultaneously influence Tax Aggressiveness. Fixed Asset Intensity partially influences Tax Aggressiveness, while the Audit Committee) partially does not affect Tax Aggressiveness, Capital Intensity partially does not affect Tax Aggressiveness, and Company Size partially does not affect Tax Aggressiveness. Keywords: Audit Commite; Capital Intensity; Firm Size; Fixed Asset Intensity; and Tax Aggresiveness.